RELATIONSHIP OF MOTHER'S KNOWLEDGE ABOUT DENTAL CARE WITH THE EVENT OF DENTAL CARE IN THREE - 5 YEARS OF AGE IN TUNAS HARAPAN GROBOGAN PAUD JIWAN MADIUN - Lilis Suryani (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2019)
Based on provisional observations in 20017 at PAUD Tunas Harapan, Grobogan Village, Jiwan, Madiun, it was found that 16% of children suffered from dental caries. This study aims to determine the relationship between maternal knowledge about dental care and the incidence of dental caries. The design of this study was cross-sectional. The sample was selected by simple random sampling technique. Data were collected using a questionnaire. In order to determine the relationship between maternal knowledge about dental care and the incidence of dental caries, a hypothesis test was carried out using the Fisher exact test. Hypothesis test results showed that p-value = 0.2, so it was concluded that there was no relationship between maternal knowledge about dental care and the incidence of dental caries. Keywords: knowledge; dental care; caries teeth ABSTRAK Berdasarkan hasil pengamatan sementara pada tahun 20017 di PAUD Tunas Harapan, Desa Grobogan, Jiwan, Madiun, didapapatkan bahwa 16% anak menderita karies gigi. Penelitian ini bertujuan mengetahui hubungan antara pengetahuan ibu tentang perawatan gigi dengan kejadian karies gigi. Desain penelitian ini adalah cross-sectional. Sampel dipilih dengan teknik simple random sampling. Pengambilan data dilakukan menggunakan kuesioner. Dalam rangka mengetahui hubungan antara pengetahuan ibu tentang perawatan gigi dengan kejadian karies gigi dilakukan uji hipotesis menggunakan Fisher exact test. Hasil uji hipotesis menunjukkan bahwa p-value = 0,2, sehingga disimpulkan bahwa tidak ada hubungan antara pengetahuan ibu tentang perawatan gigi dengan kejadian karies gigi. Kata kunci: pengetahuan; perawatan gigi; caries gigi